2000
DOI: 10.1111/0021-8294.00029
|View full text |Cite
|
Sign up to set email alerts
|

Religious Attributions and Proximity of Influence: An Investigation of Direct Interventions and Distal Explanations

Abstract: Investigations into religious attributions have focused on attributer's immediate, proximal causes of events, paying little attention to underlying, distal explanations. In an effort to explain the relatively low incidence of religious attributions and further a new model of proximal-distal attributions, we present two experiments investigating the proximal and distal use of religious and nonreligious supernatural attributions. Participants in both studies were presented a series of sixteen vignettes that vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 16 publications
(30 reference statements)
2
35
0
Order By: Relevance
“…Particularly, the semantic and intentional properties of The Franciscan Prayer related to empathy and cooperation may be held by nonbelievers, revealing that atheists make intentional and social attributions just as religious people do. However, believers may turn to God when justifying social support while nonbelievers turn to personal and social elements linked to more general human qualities (Weeks and Lupfer, 2000). Therefore, even though the Franciscan Prayer is a clearly religious text, the evoked thoughts, emotions, and actions may allow for self-reflection and social actions needed for support groups, as indicated in the Franciscan tradition and the AA's proposals.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the semantic and intentional properties of The Franciscan Prayer related to empathy and cooperation may be held by nonbelievers, revealing that atheists make intentional and social attributions just as religious people do. However, believers may turn to God when justifying social support while nonbelievers turn to personal and social elements linked to more general human qualities (Weeks and Lupfer, 2000). Therefore, even though the Franciscan Prayer is a clearly religious text, the evoked thoughts, emotions, and actions may allow for self-reflection and social actions needed for support groups, as indicated in the Franciscan tradition and the AA's proposals.…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on the role of concept acquisition, this work may be overshadowing more fundamental questions about the natural foundations of religion -questions raised in section 3 (Souls and intelligent design). For example, Atran and Norenzayan's (2004) model fails to account for people's tendency to assume that supernatural agents are responsible for traumatic life events (Deridder et al 1999;McAdams 2001;Pepitone & Saffioti 1997;Weeks & Lupfer 2000). How can reasoning about the supernatural causes of, say, suffering a miscarriage, being felled by disease, or losing a loved one in an accident be triggered by facial-recognition and body-movement recognition schemata?…”
Section: Meaning Morality and The Afterlifementioning
confidence: 99%
“…But this "god-of-thegaps" hypothesis has now been disconfirmed in social psychology experiments (see Weeks & Lupfer [2000] for an account of distal-proximal attributions to God). Moreover, the argument that scientific or secular explanations "replace" more naïve or irrational supernatural explanations is intuitively unpersuasive; obviously they can occur alongside one another (e.g., Subbotsky 2001).…”
Section: R31 Global Secularization Cannot Extirpate a True Psycholomentioning
confidence: 99%
“…Prior studies have not shown consistent associations with gender, ethnicity, or religiousness (Exline et al 2011;Wood et al 2010). Granted, people who are more religious are more likely to see God as the cause of events in general (e.g., Gorsuch and Smith 1983;Weeks and Lupfer 2000), including negative events (Gray and Wegner 2010;Hale-Smith et al 2012); however, they typically see God's intent as positive, which attenuates or at least dilutes angry feelings to some degree (Exline et al 2011;Wilt et al 2017).…”
Section: Key Findings On Anger Toward God From Predominantly Christiamentioning
confidence: 92%